A programme ‘Professor With The Public’ promotes sharing of expertise - UMP, PNC
In a move to inculcate the practise of knowledge sharing, Universiti Malaysia Pahang (UMP) organised a programme ‘Professor and the Public’ by presenting two academicians – UMP Deputy Vice-Chancellor (Academic & International), Professor Dato’ Ir. Dr. Badhrulhisham Abdul Aziz and Professor Dr. Mohd. Ridzuan Nordin from the Faculty of Industrial Sciences & Technology (FSTI).